Time-Restricted Feeding a High-fat Diet in Mice Elevates Hepatic Long-Chain Polyunsaturated Fatty Acid Content and Modifies the Triacylglyceryl Lipidome (P21-013-19). (13th June 2019) - Mehus, Aaron; Idso, Joseph; Bukowski, Michael; Picklo, Matthew
Abstract: Objectives: Obesity is associated with several diseases such as cardiovascular disease and non-alcoholic fatty liver disease. Time-restricted feeding (TRF) is effective in reducing adiposity and lessening the co-morbidities of obesity. We have demonstrated that mice consuming a high-fat (HF) diet (48%en fat), primarily composed of long chain saturated fatty acids display elevated content of hepatic triacylglycerol (TAG) and the long-chain polyunsaturated fatty acids (LCPUFAs) arachidonic acid (20:4n6, ARA) and docosahexaenoic acid (22:6n-3, DHA). We tested the hypothesis that TRF of the HF diet reduces adiposity and hepatic TAG content while maintaining elevated hepatic LCPUFA concentrations compared to mice eating the HF diet ad libitum. Methods: Male mice (12 weeks old) were fed (12 weeks) a low-fat diet ad libitum (LF-AL, 16%en fat) or a HF diet (48%en fat) either ad libitum (HF-AL) or restricted to feeding for 12 hours per day during the dark phase (HF-TRF). Fasting blood glucose and plasma insulin were measured. Plasma and hepatic levels of TAG and cholesterol were analyzed. Hepatic gene expression of mediators of de novo lipogenesis (DNL) and the circadian rhythm were examined using qPCR. Fatty acid methyl ester (FAME) analysis determined fatty acid content within the livers. Results: Blood glucose, plasma insulin, and plasma cholesterol were elevated in the HF-AL group, but were attenuated by TRF. Intake of the HF diet elevated hepatic ARA and DHA content over that of the LF diet. Hepatic TAG content, while elevated in the HF-AL mice, was not different between HF-TRF and LF-AL mice. HF-AL mice had a greater body mass and % body fat than the LF-AL and HF-TRF animals. Lipidomic analysis coupled with multivariate analysis of hepatic TAG species demonstrated TRF induced distinct differences between the TAG structures and their concentrations. Hepatic gene expression of several DNL mediators were reduced by HF-AL intake and were further reduced within the HF-TRF group. TRF restored or partially restored mRNA levels of several circadian genes altered by the HF-AL diet. Conclusions: These data suggest that limiting HF diet intake to certain hours of the day ameliorates comorbidities associated with obesity, modifies hepatic lipidomic composition, and increases the hepatic content of LCPUFA. Funding Sources: This work was supported by USDA-ARS project 3062-51000-053-00D.